AN ANALYSIS OF TEACHER STRATEGIES IN TEACHING READING AT THE FIRST YEARS STUDENTS OF SMK 2 GERUNG IN ACADEMIC YEAR 2016/2017 - Muhammad Hudri (Muhammadiyah University of Mataram, 2017)
This study is aimed to find out teachers strategies in teaching reading at SMK 2 Gerung West Lombok. It was conducted to get detailed information about the strategies used by teachers in teaching reading comprehension. This study employed a qualitative research design which is included as a case study using two data collection techniques; observation and interview. The object of this study was the teacher for the first year. Interviews were used to support the data gathered from classroom observation. All of the data were analyzed by using three major phases of analyses: data reduction, data display, and conclusion drawing and verification. This study revealed that the teachers used three strategies in teaching reading at SMK 2 Gerung West Lombok, the first is Memorizing strategy where the students must memorize five vocabularies every meeting. Secondly is Question Answer Relationship. This strategy used by the teacher to know the students understand or not. The third strategy is Game this strategy used by the teacher to motivate students in teaching reading process.